A Sectorial Analysis of Possible Information leakages prior to Merger and Acquisition Deals in Istanbul Stock Exchange - Sıtkı Sönmezer (Journal of Economics and Political Economy, 2014)
This study aims to track insider trading activities prior to announcement of merger and acquisition deals in Istanbul Stock Exchange. 35 companies and 50 deals are examined for the period 2002 -2013 and significant average abnormal returns one months to twelve months prior to the dissemination of the related information are detected, indicating private information becoming public in some way. Abnormal price changes in M&A deals in Turkey may call for closer monitoring, stricter legislations and more cautious investors in the market. Significant returns are detected but no evidence regarding with sectorial differences are found in terms of information leakage.
Keywords: E40; E44; E52; 330; Mergers; Acquisitions; Insider Trading